PENGARUH PENDEKATAN PEMBELAJARAN KONTEKSTUAL BERBASIS MULTIMEDIA TERHADAP KEMAMPUAN PEMAHAMAN MATEMATIS SISWA SMP - Siti Indah Fauziah; Luvy Sylviana Zanthy; Rano Kuswoyo (Journal on Education, 2019)
Many approaches that can be used to improve students' mathematical understanding skills include multimedia-based contextual approaches. Multimedia-based contextual approach is a natural learning approach, in accordance with the process of discovery and development of science, closely related to the real world, so that it is more meaningful and can serve the cognitive, affective, and psychomotor needs of students and is supported by interactive multimedia so imagination or all senses are aroused in a learning activity. The purpose of this study is to find out whether the ability of students' mathematical understanding of learning using multimedia-based contextual approaches is better than those using conventional approaches. The method used in this study is the experimental method, while the research instrument is a description test. The results showed that the ability of mathematical understanding of junior high school students whose learning using multimedia-based contextual approaches was better than those using conventional approaches. Multimedia-based contextual learning should be used as an alternative to mathematics learning, especially selected and essential topics in mathematics.